TARI-TARIAN LITURGI BULAN BUDAYA SEBAGAI TARIAN PENERIMAAN TERHADAP “YANG LAIN” DI GMIT - Hermanus, Rio Rocky (Institut Agama Kristen Negeri Toraja, 2025)
Abstract: The context of the Evangelical Christian Church in Timor which has a diversity of tribes and cultures is an opportunity for theological efforts that are appropriate to the context. On the other hand, the theological efforts in question are theologizing to accept